Federalism and educational policies in Brazil: contexts and ruptures (Research, Society and Development, 2018)
This article aims to analyze the complexity of the Brazilian federal arrangement and the design of educational policies through the correlation of forces and disputes between spaces and institutional tensions that configure the current and recent context in the educational policies of Brazil. It is a theoretical and documentary study and had as its axis of analysis the tensions and ruptures that had as a background (direct or indirect) the National Education System and in its contribution the very system of collaboration, as specific policies of the Brazilian cooperative pact. Thus, we emphasize the role of social participation in the implementation of EC 59/2009, in the National Education Conferences (from 2010 to 2018) and in the constitution of SASE as spaces of agreement and broad and democratic dialogue. Based on this context, it was possible to highlight the ruptures with the process of affirmation of cooperative federalism in guaranteeing the right to quality public education with social and democratic participation, evidencing the necessary strengthening of federal pacts, in the face of the challenges facing the federalism and effectiveness of educational policies in Brazil.